Historical and Graphical Analysis of the Cultural Content of Early Childhood Education - Cherednichenko, Svitlana (Pedagogical Discourse, 2013)
The scientific researches (thesis) which deals with elements of cultural content of preschool education are analysed in the article. The question of cultural component content of preschool education has gained importance only in the mid 70-ies of the XXth century. The aspects of the problem have been studied by Ukrainian researchers. Attention is paid to the fact that since the mid 90-ies of XX century in the thesis besides cultural communication, cultural behavior and other elements of the cultural component are highlighted in the article. The most important problem in the research (thesis) is Ukrainian national culture in its various manifestations. It is proved that the cultural component of the contents of preschool education is an important element in the development of preschool children.